ENHANCING THE MASTERY OF LONG SERVICE BADMINTON TECHNIQUES USING THE DRILL METHOD AMONG ELEVENTH- GRADE STUDENTS AT SMA NEGERI 1 BADAR - Safrudin Fahmi; Melfa Br Nababan; Orbit Irwansyah (RADJA PUBLIKA, 2025)
This classroom action research aims to improve the mastery of long service techniques in badminton through the implementation of the drill method for eleventh-grade students at SMA Negeri 1 Badar. The study was motivated by preliminary observations indicating that a majority of students lacked proficiency in performing the long service, a fundamental skill in badminton, due to insufficient understanding of basic techniques and a lack of targeted practice. Conducted over two cycles, this collaborative research employed a systematic approach involving planning, action, observation, and reflection. Data were collected through practical skill tests and direct observation, using a structured assessment rubric, and were analyzed quantitatively using descriptive statistics. The results demonstrated a significant improvement in student performance. In the pre-action phase, only 24.24% of students (8 out of 33) achieved the